Computerised tomography and acute traumatic head injury: time for change?. Issue 2 (March 1996) - Cranshaw, J; Hughes, G; Clancy, M
Abstract : The aim was to reconsider the "Guidelines for initial management of head injury in adults"--particularly with respect to the indications for computerised tomographic (CT) scanning--suggested by "a group of neurosurgeons" over a decade ago and still followed in some accident and emergency (A&E) departments. These recommendations are placed in the context of more recent research and the increased number of A&E departments with on-site rapid access to a CT scanner but without a resident neurosurgical facility. A case can be made for an updated policy with more liberal indications for CT scanning of acutely head injured adults in peripheral A&E departments. However, calculating the cost-efficiency of more frequent use of what is now a common but relatively expensive resource would remain a challenge.